Acute respiratory distress syndrome caused by Chlamydia psittaci: a case report and literature review - Zhou, Yan; Zou, Ya; Zhou, Lu; Wei, Hua; Zou, Yong-Wei; Guo, Xi-Rui; Ye, Yong-Qin; Li, Na; Lu, Yun (Frontiers in Medicine, 2024)
Background: Psittacosis is a zoonotic disease with a low incidence rate and a lack of specificity in clinical manifestations, making it prone to be missed, misdiagnosed, and even cause delayed treatment for patients. Metagenomic next-generation sequencing (mNGS) was successfully performed for the diagnosis of a young patient with psittacosis progressing to acute respiratory distress syndrome (ARDS), and precisely targeted antibiotic treatment was promptly administered. Additionally, a comprehensive review was conducted on 68 cases of psittacosis complicated with ARDS, with the goal of improving the clinical awareness of this disease. Case Presentation: This study reports a 37-year-old young female who was infected with Chlamydia psittaci (C. psittaci) after contact with parrots and eventually developed ARDS. The patient initially developed fever and sore throat, followed by cough and expectoration. Despite receiving empirical anti-infection treatment, the condition continued to progress rapidly, and severe dyspnea developed within a short period of time. She was subsequently transferred to the intensive care unit (ICU) and underwent tracheal intubation and mechanical ventilation due to acute respiratory failure. After the DNA sequence of C. psittaci in bronchoalveolar lavage fluid (BALF) was detected through mNGS, the patient received targeted antibiotic treatment with doxycycline and moxifloxacin, and her clinical symptoms gradually improved. Conclusions: Epidemiological investigations and the application of mNGS are crucial for the early identification and diagnosis of psittacosis. For suspected psittacosis patients, the application of mNGS technology could promote early identification of pathogens and targeted antimicrobial therapy, which might improve patient prognosis. In addition, young psittacosis patients without underlying disease should also be vigilant about the possibility of developing severe cases.